2019
DOI: 10.1186/s12891-019-2637-6
|View full text |Cite
|
Sign up to set email alerts
|

Fast track hip fracture care and mortality – an observational study of 2230 patients

Abstract: Background Hip fracture patients are frail and have a high mortality. We investigated whether the introduction of fast track care reduced the 30-day mortality after hip fractures. Methods Fast track hip fracture care was established at our institution in October 2013. Data from the Norwegian Hip Fracture Register and electronic hospital records were merged for 2230 hip fracture patients operated in our department from January 2012 through December 2015. 1090 of these pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
65
1
4

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(74 citation statements)
references
References 32 publications
4
65
1
4
Order By: Relevance
“…This result is in line with a Danish study where 30-day readmission rates were similar (ca. 12%) in fast-track group and conventional care group (LOS approximately 5 days in both groups) [26]. On the other hand, it is possible that patients who had short LOS were healthier and hence better suited for surgery and discharge without additional interventions, which could explain both LOS as well as lower 30-day readmission rate.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…This result is in line with a Danish study where 30-day readmission rates were similar (ca. 12%) in fast-track group and conventional care group (LOS approximately 5 days in both groups) [26]. On the other hand, it is possible that patients who had short LOS were healthier and hence better suited for surgery and discharge without additional interventions, which could explain both LOS as well as lower 30-day readmission rate.…”
Section: Discussionmentioning
confidence: 95%
“…However, in previous studies the length of orthogeriatric intervention has ranged from days to weeks, whereas in our tertiary care center the LOS is only 1-2 days after which the patients are discharged to an orthogeriatric secondary care ward or to primary health care wards. There are some data concerning fast track hip fracture care with short postoperative hospitalization [26] but its effect on readmissions and value of geriatric contribution in the operating unit are unclear.…”
Section: Introductionmentioning
confidence: 99%
“…The American Academy of Orthopaedic Surgeons recommends surgery within 48 hours of hospital admission (AAOS 2014). One way to attempt to decrease waiting time to surgery is to institute "fast track care" for patients with hip fracture, often consisting of attempts at early recognition of the hip fracture and thereafter expedient admission to the hospital ward, sometimes bypassing the emergency room entirely (Larsson et al 2016, Pollmann et al 2019 It is not known how, and if, waiting longer than 24 hours for surgery was associated with increased mortality compared with waiting less than 24 hours for surgery for patients with hip fractures in Sweden in recent years. It is further possible that the inconsistent results in previous studies on the risks of adverse outcomes due to prolonged waiting time to surgery may be due to different population characteristics of the study Background and purpose -Waiting time to surgery for patients with hip fractures and its potential association with mortality has been frequently studied with the hypothesis that longer waiting time is associated with adverse outcomes.…”
mentioning
confidence: 99%
“…Based on these observations, it is clear that there are a number of challenges that need to be overcome in order to improve compliance with BOA guideline 1, noticeably, the commencement of an integrated hip fracture care pathway. Pollmann et al describe a system in a similar institution to ours and have demonstrated ward transfer times of 1.1 hours and time to surgery of 23 hours in patients via a standardized fast track pathway through the ED to the ward [13]. Larsson et al describe a system where the patients' initial diagnostic X-ray is expedited based on paramedic assessment, and this has been shown to statistically reduce time to ward transfer [14].…”
Section: Discussionmentioning
confidence: 86%